Synthesis, characterisation and electrochemistry of derivatisable novel -tetra 7-oxycoumarin-3-carboxylate-substituted metallophthalocyanines - ÖZKAYA, ALİ RIZA (TAYLOR & FRANCIS LTD, 2011)
Novel -tetra-substituted metallophthalocyanines (ZnPc (3), CoPc (4), CuPc (5) and NiPc (6)) have been synthesised by cyclotetramerisation of a novel ligand, ethyl 7-(2,3-dicyanophenoxy)coumarin-3-carboxylate, with the relevant metal acetates. In addition, two derivatives of 3, slightly water-soluble tetrakis[7-oxycoumarin-3-carboxylic acid] phthalocyaninatozinc(II) and tetrakis[7-oxo-3-(ethyl piperidine-3-carboxlate)-coumarin]phthalocyaninatozinc(II), were prepared by its reaction with HCl (37%) and heating with ethyl 3-piperidinecarboxylate, respectively. The newly prepared compounds have been characterised by FT-IR, UV-vis, MALDI-TOF mass and 1H NMR spectroscopies. The redox behaviour of 3-6 was also investigated by voltammetry and in situ spectroelectrochemistry.
Keywords: metallophthalocyanine; coumarin; alpha substitution; ethyl nipecotate; electrochemistry; METAL-FREE; PHTHALOCYANINES; ACID; SPECTROELECTROCHEMISTRY; ANTIFUNGAL; COMPLEXES; COUMARIN